Sumber Daya Air Sebagai Salah Satu Faktor Alam Penunjang Harapan Hidup Tinggi Masyarakat Jepang - Trahutami, Sri Wahyu Istana (KIRYOKU, 2021)
Over time, the population growth in most countries comes from the elderly. One of them is Japan, which is known as a country with the older adults with a low mortality rate. This is evident from data from 50 countries with the highest number of older adults according to demographic data analysis from the PRB (Population Reference Bureau); Japan is in the first rank with the highest percentage of older adults aged 65 years and over in March 2020. This study aims to describe water as a natural resource to support the high life expectancy of the Japanese people. The method used in this research is the descriptive method. The data is collected through a literature study. This research shows that water in Japan is based on culture, religion, and health. As well as technological advances in Japan, water often supports technology-based innovations.